Spatio-temporal water dynamics in mature Banksia menziesii trees during drought - Bader, M.; Ehrenbergher, W.; Bitter, R.; Stevens, J.; Miller, Ben; Chopard, J.; Ruger, S.; Hardy, G.; Poot, P.; Dixon, Kingsley; Zimmermann, U.; Veneklaas, E. (Blackwell Publishing, 2014)
Southwest Australian Banksia woodlands are highly diverse plant communities that are threatened by drought- or temperature-induced mortality due to the region's changing climate. We examined water relations in dominant Banksia menziesii R. Br. trees using magnetic leaf patch clamp pressure (ZIM-) probes that allow continuous, real-time monitoring of leaf water status. Multiple ZIM-probes across the crown were complemented by traditional ecophysiological measurements. During summer, early stomatal downregulation of transpiration prevented midday balancing pressures from exceeding 2.5 MPa. Diurnal patterns of ZIM-probe and pressure chamber readings agreed reasonably well, however, ZIM-probes recorded short-term dynamics, which are impossible to capture using a pressure chamber. Simultaneous recordings of three ZIM-probes evenly spaced along leaf laminas revealed intrafoliar turgor gradients, which, however, did not develop in a strictly basi- or acropetal fashion and varied with cardinal direction. Drought stress manifested as increasing daily signal amplitude (low leaf water status) and occasionally as rising baseline at night (delayed rehydration). These symptoms occurred more often locally than across the entire crown. Microclimate effects on leaf water status were strongest in crown regions experiencing peak morning radiation (East and North). Extreme spring temperatures preceded the sudden death of B. menziesii trees, suggesting a temperature- or humidity-related tipping point causing rapid hydraulic failure as evidenced by collapsing ZIM-probe readings from an affected tree. In a warmer and drier future, increased frequency of B. menziesii mortality will result in significantly altered community structure and ecosystem function.